A Survey of the Relationship between Earnings Management and Qualified Auditor Opinion in Tehran Stock Exchange - Abolverdi, Zahra; Kheradmand, Ali (International Journal of Economics and Financial Issues, 2017)
This study aims to evaluate the effect of earnings management on type of auditor report in the companies listed on Tehran Stock Exchange (TSE). To measure earnings management, the modified Jones model based on discretionary accruals is used. The audit report is qualified opinion due to the uncertainty in activity and qualified report due to some reasons except uncertainty in going concern. To test the study hypotheses, the data of 80 companies listed on TSE are used as study sample during 2009-2013 by logistic regression model. In the present study, besides testing the relationship between earnings management and qualified auditor opinion, the effect of financial distresses on the relevant relationship is studied. The results of study show the positive and significant relationship between earnings management and qualified opinion regarding some items except going-concern uncertainty. There is no significant relationship between earnings management and qualified opinion in financially distressed companies. Keywords: Earnings management, Qualified audit opinion, Going-concern uncertainty, Financially distressed companies JEL Classifications: D53, M42